Reframing Heart of Darkness as Science Fiction. Issue 1 (1st January 2015) - Lavender, Isiah
<x content-type="archive" xml:space="preserve">Abstract</x> This essay reframes the discussion of Heart of Darkness as an exploration of its specific resonances with sf through sf's megatext. To accomplish this task, I first make clearer what it means to read a non-sf text science-fictionally, as a work of science fiction. Next, I concentrate on the sf megatext through proto-sf and Conrad's relationship to it. Finally, I demonstrate the consequences of this alien colonial encounter between Kurtz, Marlow, and the African continent. Placing Heart of Darkness in conversation with the proto-sf of its time adds a useful dimension to the narrative. The novella's sf concerns were once consonant with the emerging modernist ethos regarding race, colonialism, and the alien other, before it became more associated with the "high modernism" of Joyce. Put another way, Conrad adapts the sf genre to present noxious materials, thus avoiding marginalization by the literary community while simultaneously speaking modernism's new and ugly truths before modernism itself was codified. If we do not read Heart of Darkness science-fictionally, not only do we miss an interpretation in reading colonial fiction, but we also fail to spot the multimodal resonance of this text for modern consciousness—a direct reflection of "science fiction thinking" (Landon 4).